A stable self-powered ultraviolet photodetector using CH3NH3PbCl3 with weak-light detection capacity under working conditions. Issue 18 (14th April 2022) - Liu, Zhirong; Liu, Zhiyong; Sun, Qiang; Zhang, Tao; Yu, Haixuan; Zhang, Xuning; Dai, Letian; Liao, Guanglan; Shen, Yan; Zhang, Xiao-Li; Zhu, Jun; Wang, Mingkui
Abstract : An UV photodetector with a vertical-structure architecture shows a fast response time of 7.76 μs and a high on/off ratio of over 5 × 10 3, as well as a weak-light detecting ability with a specific detectivity of 7.08 × 10 11 Jones. Abstract : Organic–inorganic hybrid lead halide perovskite photodetectors have attracted worldwide attention in the field of optoelectronics. This study reports on a solution processable UV photodetector with a vertical-structure which contains a homogenous and dense layer of wide-bandgap methylammonium lead chlorine (CH3 NH3 PbCl3 ) semiconductor as a photon-response absorber. The resultant CH3 NH3 PbCl3 -based UV photodetector achieves a fast response time of 7.76 μs and a high on/off ratio of over 5 × 10 3 . In addition, the photodetector exhibits an impressive light detecting ability with a specific detectivity ( D *) of 7.08 × 10 11 Jones at an illumination intensity of 0.6 μW cm −2 at 375 nm. Moreover, CH3 NH3 PbCl3 -based UV photodetectors without encapsulation show long-term stability (1200 h with 5% attenuation) under simulated operational conditions (25 °C, and 80% relative humidity in air). In addition, the CH3 NH3 PbCl3 -based photodetectors are proven to adapt to flexible substrates such as polyethylene naphthalate. This work reveals great potential of photodetectors with wide bandgap perovskites in the applications of UV light detection.